THE EFFECT OF INTELLECTUAL CAPITAL AND CORPORATE SOCIAL RESPONSIBILITY ON FIRM VALUE - Ni Made Sunarsih; Ni Putu Shinta Dewi (AIBPM Publisher, 2019)
Company value is a certain condition that has been achieved by the company, which describes the investor's perception of management's performance in managing the company. The long-term goal of the formation of a company is to maximize the value of the company, by increasing the prosperity of the owners or shareholders (stakeholders). The higher the stock price of a company, the higher the profit of the stakeholders, which is reflected in the higher value of the company. In this study the value of the company is proxied by Price to Book Value (PBV). This study aims to determine the Effect of Intellectual Capital and Corporate Social Responsibility on the Value of Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) during the period 2015-2017. The total sample of this study is 204 manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. Determination of samples using purposive sampling method. The analysis technique used is multiple linear analysis.The results of this study indicate that the variables of Intellectual Capital and Corporate Social Responsibility have a positive effect on firm value (PBV).